2013
DOI: 10.1002/wrcr.20130
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to account for fracture aperture variability when modeling solute transport in fracture networks

Abstract: [1] A simple yet effective method is presented to include the effects of fracture aperture variability into the modeling of solute transport in fracture networks with matrix diffusion and linear sorption. Variable apertures cause different degrees of flow channeling, which in turn influence the contact area available for these retarding processes. Our approach is based on the concept of specific flow-wetted surface (sFWS), which is the fraction of the contact area over the total fracture surface area. Larsson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…This can have a considerable impact on the retardation in the fracture. Larsson et al [2013] showed how sFWS can be included in DFN modeling. Water Resources Research…”
Section: Mathematical and Numerical Approaches To Modeling Of Flow Anmentioning
confidence: 99%
“…This can have a considerable impact on the retardation in the fracture. Larsson et al [2013] showed how sFWS can be included in DFN modeling. Water Resources Research…”
Section: Mathematical and Numerical Approaches To Modeling Of Flow Anmentioning
confidence: 99%
“…Thus, aperture variation over each fracture is not accounted for. This aperture variation is what gives rise to flow channeling effect (Larsson et al., 2013). In the CNM, the channeling effect is accounted for directly by channels determined through the calibration process.…”
Section: Predictions Of Long‐term Tracer Transport Based On Calibrate...mentioning
confidence: 99%
“…More recent improvements in DF model equations (Shahkarami et al, 2019) include the non-equilibrium pollutant transport in fractures by coupling the kinetic equation of the pollutant mass adsorption-desorption and diffusion into the rock matrix or in the lateral dead-ends of fractures, to the advection-dispersion transport equation. Furthermore, for the reactive pollutant transport in fractures, a simple and efficient method was presented by Larsson et al (2013) to account for the effects of the specific flow-wetted surface (sFWS) during pollutant transport with reactions. This sFWS is the fraction of the fracture wall contact area where pollutant adsorption occurs during the transport in fractures of DFN.…”
Section: Pollutant Transport Into a Single Fracture Of The Df Modelmentioning
confidence: 99%
“…Furthermore, for the reactive pollutant transport in fractures, a simple and efficient method was presented by Larsson et al. (2013) to account for the effects of the specific flow‐wetted surface (sFWS) during pollutant transport with reactions. This sFWS is the fraction of the fracture wall contact area where pollutant adsorption occurs during the transport in fractures of DFN.…”
Section: Implementation Of New Flow and Transport Equationsmentioning
confidence: 99%